1993
DOI: 10.1099/0022-1317-74-9-1837
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide and predicted amino acid sequences of Marek's disease virus homologues of herpes simplex virus major tegument proteins

Abstract: The DNA sequence of an 8-4kbp BamHI-EcoRI fragment of Marek's disease virus (MDV) strain GA was determined. Three of the predicted polypeptides are homologous to UL47, UL48 and UL49 encoding the major tegument proteins of herpes simplex virus type 1 (HSV-1), and four are homologous to HSV-1 UL45, UL46, UL49-5 and UL50. These seven genes are found in the long unique region of the MDV genome and are collinear with homologues in HSV-1 and varicella-zoster virus (VZV). Northern blot analysis revealed different tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…MDV2 UL48 protein has a rather high homology with the HSV-1 UL48 protein, which was reported as a transactivator of immediate-early gene expression after virus infection (Roizman & Sears, 1996). When compared with MDV1 UL48 protein (Yanagida et al, 1993), high homology is found in the acidic domain (residues 1 to 60) and the prolinerich domain (residues 60 to 100) in the N-terminal region of MDV2. However, the MDV2 UL48 protein lacks a region corresponding to the C-terminal activation domain of the HSV-1 UL48 gene product similar to those of VZV, HVT and MDV1 (data not shown).…”
Section: Bjjimentioning
confidence: 99%
See 3 more Smart Citations
“…MDV2 UL48 protein has a rather high homology with the HSV-1 UL48 protein, which was reported as a transactivator of immediate-early gene expression after virus infection (Roizman & Sears, 1996). When compared with MDV1 UL48 protein (Yanagida et al, 1993), high homology is found in the acidic domain (residues 1 to 60) and the prolinerich domain (residues 60 to 100) in the N-terminal region of MDV2. However, the MDV2 UL48 protein lacks a region corresponding to the C-terminal activation domain of the HSV-1 UL48 gene product similar to those of VZV, HVT and MDV1 (data not shown).…”
Section: Bjjimentioning
confidence: 99%
“…The UL49.5 proteins of PRV and BHV-1 are structural components of the viral envelope Liang et al, 1996). The MDV2 UL49.5 gene encodes a 95 amino acid protein with 71 % identity to that of MDV1 (Yanagida et al, 1993), exhibiting characteristics of a membrane protein without a consensus N-glycosylation sequence as described elsewhere (Barnett et al, 1992 ;. The deduced protein of MDV2 UL50 exhibited homology to dUTPase of other alphaherpesviruses.…”
Section: Bjjimentioning
confidence: 99%
See 2 more Smart Citations
“…(A) Schematic representation of VP16 homologs from five herpesviruses and delineation of the VP16-core protein used for crystallography. The VP16 homologs are derived from HSV-1 (strain 17; Campbell et al 1984;Dalrymple et al 1985), VZV (Davison and Scott 1986), GHV-1 (Yanagida et al 1993), EHV-1 (Telford et al 1992), and BHV-1 (Carpenter and Misra 1992). A conserved VP16-core region is shown in dark gray and the carboxy-terminal HSV-1 transcriptional activation domain (AD) is shown in light gray.…”
Section: A Conserved Vp16 Corementioning
confidence: 99%